Effect of Stiffness on Performance of Diaphragm Wall. (2015) - B, Yajnheswaran; P.R, Akshay; C, Rajasekaran; Rao, Subba
Abstract: Diaphragm walls are generally constructed using stiff concrete of same stiffness throughout. Research has shown that as wall flexibility increases, the stress imposed by the soil redistribute and reduces structural forces on wall. Approximately five fold reduction in maximum bending moment occurred when wall stiffness was reduced from that of a 1m concrete section to that of a Frodinghamn1N sheet pile. Unfortunately this beneficial effect is accompanied by greater wall and soil movements (Potts & Day, 1991). So the diaphragm wall cannot be too flexible also. In this paper static analysis of two different diaphragm wall sections of varying stiffness is carried out using PLAXIS software for the load condition existing at deep draft berth of New Mangalore Port, and the performances of these sections are compared with previous study performed by Yajnheswaran et al. (2015). The diaphragm wall sections used in analysis are modeled as single panel. The length of the panel is taken as 5m. Anchors are provided at +2.5m. Soil layer details are obtained from boreholes at NMPT.